Correction: Advanced anti-corrosion coatings prepared from α-zirconium phosphate/polyurethane nanocomposites. Issue 36 (24th April 2017) - Huang, Tsao-Cheng; Lai, Guan-Hui; Li, Chen-En; Tsai, Mei-Hui; Wang, Peng-Yun; Chung, Yi-Hsiu; Lin, Meng-Hung
Abstract : Correction for 'Advanced anti-corrosion coatings prepared from α-zirconium phosphate/polyurethane nanocomposites' by Tsao-Cheng Huang et al., RSC Adv., 2017, 7, 9908–9913.